Pelatihan Buketpreneurship Guna Membangun Keterampilan Entrepreneur Menuju Wirausaha Unggul - Islami, Intan Bungo; Rahma, Laila; Rizqiyah, Rofiatur; Dzilkamil, Khabibah; Adinugraha, Hendri Hermawan (Welfare : Jurnal Pengabdian Masyarakat, 2024)
In accordance with the theme of this training, namely "Develop Creativity Towards Quality Entrepreneurs", which aims to explore and analyze opportunities that can be taken by students in developing superior entrepreneurship through bouquetpreneurship training. Apart from that, building networks and collaboration through interaction with business practitioners and strengthening the role of students as agents of economic change. The method used in this service is a direct training method or course for students who act as service subjects consisting of students who have the interest and potential to develop entrepreneurial skills. Where participants will be guided to implement the understanding gained in accordance with established standards or guidelines. The results of this training can make a significant contribution to students' understanding of potential entrepreneurial opportunities in the contemporary era. Apart from that, it is hoped that this bouquetpreneurship training can become an effective model in improving entrepreneurial skills and spirit and being able to become an agent of change who brings innovation to overcome global economic challenges.